Kontribusi Kitab Sawi dalam Sastra Sufi dan Budaya Sasak: Perspektif Scheleiermacher - Hasanuddin Chaer; Zulkarnaen Zulkarnaen; Mari'i Mari'i; Aswandikari Aswandikari; Murahim Murahim; Muh. Yusron Ridyasmara (Universitas Hamzanwadi, 2024)
This article aims to interpret two aspects of the Kitab Sawi: its grammatical structure and psychological meaning, uncovering both linguistic and psychological dimensions within this Sufi literary text. The subject of this study is the Sufi manuscript Kitab Sawi. To achieve this goal, the article adopts Schleiermacher's hermeneutic theory with a descriptive-analytical approach. The research follows four stages: data collection, data processing, interpretation, and drawing conclusions. The study reveals that the Kitab Sawi manuscript focuses on two main aspects: grammatical structure and psychological meaning. Key insights from the Kitab Sawi, which serves as the primary source for this article, include the following: a) Source of Ethical-Religious Literary Knowledge: The Kitab Sawi manuscript contains strong elements of Sufi literature, aimed at conveying moral and ethical values rooted in religious teachings. b) The Importance of Cultural Heritage: Kitab Sawi is not only valuable as a literary work but also as a representation of past intellectual and spiritual wealth. This manuscript plays a vital role in preserving and communicating cultural and spiritual teachings across generations. c) Psychological and Structural Significance: The analysis demonstrates that Kitab Sawi features a profound and intricate grammatical structure, characteristic of Sufi thought, which frequently employs symbolic and metaphorical language. This structure adds a psychological depth, allowing readers to undergo spiritual transformation through contemplation and engagement with the text. In conclusion, this article offers valuable contributions to the understanding of Sufi literature and Sasak cultural heritage.